Occupation and sports participation as risk factors for the development and progression of knee osteoarthritis - Yousuf, Amjad Waheed; Yousuf, Awhad Mueed; Erum, Aasiy Ul (International Journal of Research in Medical Sciences, 2017)
Knee Osteoarthritis (OA) is a major cause of pain and disability worldwide. In majority of cases of knee OA the etiology remains unidentified, however, a number of systemic and local biomechanical factors have been associated with the increased risk of this disorder. These factors may determine the onset of knee OA and rapidity with which the disorder progresses. Occupation and sports participation are among the commonly implicated risk factors and have been studied in detail for their relationship with knee OA. An increased risk of knee OA has been observed in people who are involved in jobs requiring bending and kneeling of the knee joint. Likewise, persons who participate in sports involving excessive strain of the knee joint also carry a higher risk of development of this disorder in the later part of their life. In this review we present the data, obtained from original resources, determining the relationship between occupation and sports participation with the onset and progression of knee OA.